2021
DOI: 10.1007/s11071-021-06431-1
|View full text |Cite
|
Sign up to set email alerts
|

PI/PID controller stabilizing sets of uncertain nonlinear systems: an efficient surrogate model-based approach

Abstract: Closed forms of stabilizing sets are generally only available for linearized systems. An innovative numerical strategy to estimate stabilizing sets of PI or PID controllers tackling (uncertain) nonlinear systems is proposed. The stability of the closed-loop system is characterized by the sign of the largest Lyapunov exponent (LLE). In this framework, the bottleneck is the computational cost associated with the solution of the system, particularly including uncertainties. To overcome this issue, an adaptive sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…PI control is still one of the most successful controllers in industrial processes. However, it typically has poor control performance and stability issues for nonlinear and time-varying systems [34], especially when control actions are needed at different operating points with varying operating conditions and dynamic setpoints. The PI and fuzzy logic algorithm combination offers a promising alternative solution, in which gain parameters are adapted by weighting factors calculated through a fuzzy logic controller [35].…”
Section: Adaptive Fuzzy-pi Control Systemmentioning
confidence: 99%
“…PI control is still one of the most successful controllers in industrial processes. However, it typically has poor control performance and stability issues for nonlinear and time-varying systems [34], especially when control actions are needed at different operating points with varying operating conditions and dynamic setpoints. The PI and fuzzy logic algorithm combination offers a promising alternative solution, in which gain parameters are adapted by weighting factors calculated through a fuzzy logic controller [35].…”
Section: Adaptive Fuzzy-pi Control Systemmentioning
confidence: 99%
“…[16] has shown that DDPG can perform better than the proportion integral differential (PID) control. PID control has a fundamental limitation imposed by the instrument, designing a robust controller to uncertain sensor signals is not an easy task and the control system may suffer from large magni-tude disturbance [17]. On the other hand, DDPG may suffer from instability, high sensitivity to hyper-parameters, may converge to poor solutions, or not converge at all [18].…”
Section: Background and Related Workmentioning
confidence: 99%
“…The approach can be employed for more complex applications such as multiple outputs [2]. It has also been extended for predicting PID stabilizing sets for nonlinear systems, even including some uncertainties in [4].…”
Section: Efficient Surrogate Modelmentioning
confidence: 99%